The relationship between food consumption and intestinal microbiota in type 2 diabetic patients at a private clinic in Minas Gerais (Research, Society and Development, 2023)
Type 2 Diabetes Mellitus is a disease characterized by causing constant hyperglycemia, metabolic complications such as fatigue, polyuria, polydipsia and kidney and cardiovascular damage. Furthermore, people with type 2 Diabetes Mellitus may suffer from gastrointestinal symptoms, such as diarrhea, flatulence, nausea, vomiting and abdominal pain. It is a condition that is growing exponentially in the world and its cause is related to genetic and environmental factors, such as inadequate diet and sedentary lifestyle. The objective of this article is to present research on food consumption and its relationship with intestinal dysbiosis in a group of patients with DM2, in order to advance studies that promote a better quality of life for these affected patients. The sample was made up of 13 volunteers, between 18 and 69 years old, of both genders, with type 2 Diabetes Mellitus, from a private clinic in Minas Gerais. To evaluate the data, a questionnaire was used including anthropometric data, the Bristol Scale, the Gastrointestinal Symptom Rating Scale (GSRS) instrument to check the incidence of gastrointestinal symptoms and the Food Frequency Questionnaire (FFQ). It was possible to verify that the majority of diabetic patients were overweight or some degree of obesity and also reported gastrointestinal symptoms, such as diarrhea, constipation, flatulence, heartburn, reflux and nausea, with the consumption of milk and dairy products, fruits, red and white meat, cake and cheese bread and seeds. Therefore, understanding the dietary pattern and management of symptoms is fundamental to improving the quality of life of patients with type 2 Diabetes Mellitus.